Highly selective and efficient olefin epoxidation with pure inorganic-ligand supported iron catalysts. Issue 37 (11th September 2019) - Zhou, Zhuohong; Dai, Guoyong; Ru, Shi; Yu, Han; Wei, Yongge
Abstract : An inorganic ligand-supported iron catalyst, which can effectively catalyze olefin epoxidation with excellent yields. Abstract : Over the past two decades, there have been major developments in the transition iron-catalyzed selective oxidation of alkenes to epoxides; a common structure found in drug, isolated natural products, and fine chemicals. Many of these approaches have enabled highly efficient and selective epoxidation of alkenes via the design of specialized ligands, which facilitates to control the activity and selectivity of the reactions catalyzed by iron atom. Herein, we report the development of the olefin epoxidation with inorganic-ligand supported iron-catalysts using 30% H2 O2 as an oxidant, and the mechanism is similar to iron-porphyrin type. With the catalyst1, (NH4 )3 [FeMo6 O18 (OH)6 ], various aromatic and aliphatic alkenes were successfully transformed into the corresponding epoxides with excellent yields as well as chemo- and stereo-selectivity. This catalytic system possesses the advantages of being able to avoid the use of expensive, toxic, air/moisture sensitive and commercially unavailable organic ligands. The generality of this methodology is simple to operate and exhibits high catalytic activity as well as excellent stability, which gives it the potential to be used on an industrial scale, and maybe opens a way for the catalytic oxidation reaction via inorganic-ligand coordinated iron catalysis.